Pain Management: Patients' Perspective - N. Regeh; F. Ahmadi; E. Mohammadi; A. Kazem nejad; M. Anoosheh (Iran University of Medical Sciences, 2007)
Background & Aim: Pain relief is an integral part of nursing care and an appreciated outcome of nursing actions . Pain is one of the most common problems in postoperative period. This article is part of a larger study which aimed to explore patients' perspective of pain and pain management. Annually, more than hundreds of million people undergo surgical operations experiencing postoperative pain. Although a number of researches and discussion papers have explored the issue, the current study has explored patients' perspective about postoperative pain management, a subject that have rarely been studied.  Material & Method: A qualitative approach was adopted. Data was collected via semi- structured interviews and participations' observations. A purposive sample of ten surgical patients and four companions (relatives) were selected from two educational health centers. Data analysis uncovered a number of themes. The themes related to patients' perspective about pain management is subject of this paper.  Results: The other five themes of pain management were: watching over by personnel and availability, humanistic approach, presenting information and patient education, communication and patient's participation, considering patient integrity, and ambivalence between expression of pain and reluctance.  Conclusion: The findings of this study help personnel to know the patients and their needs better and to find what pain management means to them. Consequently, nurses can plan, imply and evaluate nursing interventions most appropriately